Sea Turtle Captivity as Tourism Education Media in Jengglungharjo, Tanggunggunung, Tulungagung Regency - Wahyu Nurhayati, Dwi Astuti (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2024)
This research aims at captivating sea turtles as one media which was used as tourism education to teach children around the Jengglungharjo Village. The rescue efforts for sea turtles were conducted to protect them as one of endangered animals. The current study was deployed descriptive qualitative method as collaborative research between the researcher and POKDARWIS. The data were gained through displaying direct observations of how turtle imprisonment was made from bamboo on the Sanggar Beach. According to the findings of the investigation, the village of Jengglungharjo boasts an intriguing and unspoiled tourist destination that features three different species of turtles, including belimbing, green, and shell turtles. The children around of Jengglungharjo village could learn them as tourism education media as realia. By preserving or captivating the sea turtles most of the people not only the adults but also the children was aware how important these different species of turtle to balance of the sea habitat, then by preserving the sea turtles eggs inside bamboo fence could be one media of tourist destination which enhance their economic income and scientific knowledge.